2017
DOI: 10.1073/pnas.1621172114
|View full text |Cite
|
Sign up to set email alerts
|

Mitogenic stimulation accelerates influenza-induced mortality by increasing susceptibility of alveolar type II cells to infection

Abstract: Development of pneumonia is the most lethal consequence of influenza, increasing mortality more than 50-fold compared with uncomplicated infection. The spread of viral infection from conducting airways to the alveolar epithelium is therefore a pivotal event in influenza pathogenesis. We found that mitogenic stimulation with keratinocyte growth factor (KGF) markedly accelerated mortality after infectious challenge with influenza A virus (IAV). Coadministration of KGF with IAV markedly accelerated the spread of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 52 publications
2
29
0
Order By: Relevance
“…At the first glance, the susceptibility to H7N9 infection and the susceptibility to severe H1N1 infection are not equivalent issues. In fact, H7N9 infection and severe H1N1 infection essentially shared the same pathology, i.e., viral pneumonia, the most lethal consequence of influenza (Nikolaidis et al , ). Overall, pandemic H1N1 viruses exhibit binding specificity to human‐type α2,6‐linked sialic acid receptor (Zhou et al , ); the viruses tend to replicate more actively in human bronchus than in lung tissue (Chan et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…At the first glance, the susceptibility to H7N9 infection and the susceptibility to severe H1N1 infection are not equivalent issues. In fact, H7N9 infection and severe H1N1 infection essentially shared the same pathology, i.e., viral pneumonia, the most lethal consequence of influenza (Nikolaidis et al , ). Overall, pandemic H1N1 viruses exhibit binding specificity to human‐type α2,6‐linked sialic acid receptor (Zhou et al , ); the viruses tend to replicate more actively in human bronchus than in lung tissue (Chan et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Recovery will require a vigorous innate and acquired immune response and epithelial regeneration. From my perspective, similar to influenza, administrating epithelial growth factors such as KGF might be detrimental and might increase the viral load by producing more ACE2 expressing cells [19]. Elderly individuals are particularly at risk because of their diminished immune response and reduced ability to repair the damaged epithelium.…”
Section: Stage 3: Hypoxia Ground Glass Infiltrates and Progression mentioning
confidence: 99%
“…In animal studies, rapamycin was shown to promote cross-strain protection against lethal infection with influenza virus of various subtypes when administered during immunization with influenza virus subtype H3N2 (7). Mitogenic stimulation accelerates influenza-induced mortality in animals by increasing susceptibility of alveolar type II cells to infection, and pre-treatment with rapamycin reverses this effect (8).…”
Section: Mtor and Influenzamentioning
confidence: 99%